2013
DOI: 10.1099/mic.0.070474-0
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the PTEN catalytic motif in the bacterial undecaprenyl pyrophosphate phosphatase, BacA/UppP

Abstract: Isoprenoid lipid carriers are essential in protein glycosylation and bacterial cell envelope biosynthesis. The enzymes involved in their metabolism (synthases, kinases and phosphatases) are therefore critical to cell viability. In this review, we focus on two broad groups of isoprenoid pyrophosphate phosphatases. One group, containing phosphatidic acid phosphatase motifs, includes the eukaryotic dolichyl pyrophosphate phosphatases and proposed recycling bacterial undecaprenol pyrophosphate phosphatases, PgpB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 112 publications
1
26
1
Order By: Relevance
“…In this study, we were particularly interested in two identified mutants that were highly sensitive to bacitracin and had two independent insertions in the same locus, SMU.244, which encodes a homologue of UppP required for the recycling or de novo synthesis of undecaprenyl phosphate (Up; C 55 -P) (Bickford & Nick, 2013;Chang et al, 2014;El Ghachi et al, 2004). Although the roles of UppP in cell wall biosynthesis and bacitracin resistance are well documented in E. coli, UppP homologues and their physiological features in many Gram-positive bacteria, such as S. mutans, are still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we were particularly interested in two identified mutants that were highly sensitive to bacitracin and had two independent insertions in the same locus, SMU.244, which encodes a homologue of UppP required for the recycling or de novo synthesis of undecaprenyl phosphate (Up; C 55 -P) (Bickford & Nick, 2013;Chang et al, 2014;El Ghachi et al, 2004). Although the roles of UppP in cell wall biosynthesis and bacitracin resistance are well documented in E. coli, UppP homologues and their physiological features in many Gram-positive bacteria, such as S. mutans, are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bacitracin, a cyclic polypeptide antibiotic that is produced by certain species of Bacillus, can target essential components of the cell envelope and suppresses the biosynthesis of peptidoglycan in many Gram-positive bacteria (Jordan et al, 2008). Bacitracin binds to undecaprenyl pyrophosphate (Upp), the lipid carrier responsible for the translocation of cell envelope precursors from the cytosol to the extracellular side of the cytoplasmic membrane, preventing the dephosphorylation of Upp necessary for the recycling of the lipid carrier (Bickford & Nick, 2013). Interestingly, S. mutans is known to be resistant to bacitracin and this property is often exploited in the isolation of this organism from the highly diverse oral microflora (Liljemark et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tatar et al and Touzé et al (4,9) demonstrated that the active sites of LpxT, YbjG, and PgpB are all oriented toward the periplasmic space and might participate in C 55 -PP recycling based on biochemical evidence and topology analysis. On the contrary, the topological model of UppP revealed a large cytosolic loop that is conserved in bacterial UppP enzymes, suggesting that it may participate in C 55 -PP de novo synthesis in the cytoplasm (4,10). To date, however, it is still unclear on which side of the plasma membrane the dephosphorylation of C 55 -PP molecules occurs.…”
mentioning
confidence: 99%
“…It may be advantageous, in general, for cells to have UPP-Pase activity localized to both faces of the membrane to facilitate de novo Und-P synthesis (on the inner face) and UPP recycling (on the outer face), and this may account in part for the redundancy commonly observed in UPPPases (6)(7)(8).…”
mentioning
confidence: 99%